Understanding farmed salmon imports and e-commerce consumer satisfaction in China: A text mining approach - Mausam Budhathoki; Li Lincen; Hao Xu; Wenbo Zhang; Saihong Li; Richard Newton; Danny Campbell; David Little (Journal of Agriculture and Food Research)
Salmon, a luxury aquatic species, has seen a steady increase in imports in China. The rapid development of the Internet, the transformation of consumption behaviour, and the impact of the COVID-19 pandemic have prompted consumers to purchase salmon products from e-commerce platforms in China. In this context, understanding salmon import trends and consumer satisfaction with salmon e-commerce is critical to promoting and sustaining sales of salmon products through e-commerce platforms. Therefore, this study aims to investigate the import trend analysis of salmon in China as well as understand factors influencing consumer satisfaction with salmon e-commerce. We analysed 10,064 consumer comments out of 25,763 for this study after resampling the proportion of positive/negative comments. Sentiment analyser, Textblob, classified 65.2 % of consumer comments as positive, 21.7 % as negative, and 13.1 % as neutral. Additionally, Latent Dirichlet Allocation (LDA) topic modelling identified five areas critical for satisfaction with salmon e-commerce: purchase decision (19.5 % of the comments), eating experience (22.3 %), service quality and delivery (20.6 %), purchase history (17.5 %), and general product quality (20 %). Our findings indicate that service quality and delivery are the most critical factors affecting consumer satisfaction, whereas purchase history has the least impact. Consumers’ PLUS membership profile, salmon product style, and preservation form had a significant influence on consumer satisfaction, while the country of origin, weight and price of the product had no significant influence. Salmon e-commerce platforms need to improve logistic service and delivery quality to influence consumer satisfaction.